2021
DOI: 10.3390/ijerph18126652
|View full text |Cite
|
Sign up to set email alerts
|

Health Education as a Means of Addressing Death in the Elderly

Abstract: Education for death is an emerging field of study in which health education research and proposals are increasingly being made with the aim of acquiring knowledge and skills to promote positive attitudes towards health and preparation for the end of life. The aim of this study is to find out what experience older people have had with death education and the importance they give to health education. A qualitative methodological design was selected using a semi-structured interview. The survey consisted of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Education undertakes the functions of cultural selection, transmission, transformation, criticism, innovation, and remodeling [53]. Life-and-death education can not only convey knowledge of life and death, but also alleviate the negative emotions towards death, help people prepare for death, and improve the quality of death [18].…”
Section: Discussionmentioning
confidence: 99%
“…Education undertakes the functions of cultural selection, transmission, transformation, criticism, innovation, and remodeling [53]. Life-and-death education can not only convey knowledge of life and death, but also alleviate the negative emotions towards death, help people prepare for death, and improve the quality of death [18].…”
Section: Discussionmentioning
confidence: 99%
“…If children cannot be properly guided at this stage, it is likely that they do not properly understand death, which may lead them to develop negative emotions, affecting their whole life ( 7 ). Therefore, death education is vital for the physical and mental development of children and adolescents: it will improve how they comprehend the world around them as grow ( 8 ) and help them to form a correct view of life and death ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The program teaches individuals how to recognize and face death [10]. The goal is to facilitate acceptance of end of life, process of death, and experience of bereavement in terms of the individual's knowledge, attitudes, and skills [11,12]. Previous studies have shown that death education promotes positive changes in death-related attitudes, enhances the sense of meaning in life, and improves the quality of life [13][14][15].…”
Section: Introductionmentioning
confidence: 99%